Use of sewage sludge ash as a cement replacement in concrete: A review / Amminudin Ab Latif, Ainamardia Nazarudin and Noor Safwan Muhamad - Ab Latif, Amminudin; Nazarudin, Ainamardia; Muhamad, Noor Safwan (Universiti Teknologi MARA Cawangan Pahang, 2020)
Rapid industrial development and population growth in countries around the world have increased the production of sewage sludge. Sewage sludge is a waste product of the sewage treatment plant processes. The sewage treatment plants produce a large volume of wastewater every day in order to control the quality of the effluent released into a river or the sea. Instead of disposing of the sewage sludge at landfills, using sewage sludge as a recycle material could minimize the need for a new disposal area and consequently reduce the negative impact on the environment. Many studies have been conducted to examine the use of sewage sludge ash as a recycle material. This paper reviews the use of sewage sludge ash as a cement replacement in concrete production. Sewage sludge ash is a powdered material that contains a high percentage of SiO2, Al2O3, Fe2O3, CaO, P2O5 and SO3, and shows moderate reactivity in terms of pozzolanicity. Most of the researchers burned the sewage sludge at a temperature range of between 600°C - 900°C to produce sewage sludge ash. The partial replacement of cement with sewage sludge ash promoted an increase in the compressive and flexural strength of concrete. Meanwhile, the replacement of 5% sewage sludge ash by weight of cement was considered to be an optimum content in obtaining the best mechanical performance of concrete. Furthermore, the workability of concrete after 28-days was improved with the addition of SSA.